Translation Techniques of Subtitling: A Case for Trolls Movie - John Pahamzah; Azkiyyatus Syariifah (Journal of English Language Teaching and Cultural Studies, 2019)
The research aims to analyze the translation techniques of subtitling used on Trolls movie. This research use a qualitative research. The content analysis is used as a method to identify and analyze the translation techniques in Trolls movie. Every utterance in five scenes of Trolls movie are the unit of analysis of this research. The source language is English and the target language is Indonesian Language. The result proves that the translation technique that mostly appears on Trolls movie (2016) is reduction with 8 data (26.67%). It seems that this technique is used to compress the information from the source language so that it will not be too long because it will be applied in subtitle; it results the shortest translation version to be applied to movie or film subtitle so that it will be easier for the viewers to catch the information and it will not distract the visual from the film that is being shown; and it can avoid the redundancy of the source language.